Pendampingan Perancangan Arsitektur Masjid Al-Hidayah dengan Integrasi Fungsi Edukasi di Kota Sibolga - Sitompul, Rabita Akbari (PT. Arsil Reka Engineering, 2025)
The role of a mosque today isn’t just as a place for prayer—it also plays an important part as an educational space for the community. The goal of this project is to create a space that meets people’s spiritual needs while also offering areas for studying, reading, and character-building activities for the younger generation in Sibolga. The design process involved visiting the site, setting up the terms of reference, analyzing data, coming up with design ideas, and developing a pre-design plan. The concept follows a minimalist and functional architectural approach, with prayer areas and learning spaces blended smoothly into one shared location. The result shows that combining these functions makes better use of space and helps strengthen the mosque’s role as a hub for community growth. Hopefully, this design can be a model for other mosques in coastal areas that may not have much land to build on but have strong community.